2012
DOI: 10.4236/fns.2012.39156
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Fatty Acid Composition of Dairy Products and Margarines with Reduced or Substituted Fat Content

Abstract: The objective of this study was to survey the fatty acid profiles of fat spreads, margarines, shortenings, vegetable fat ice creams, vegetable fat milk-based cream substitutes, vegetable fat cheese substitutes, and reduced-fat cheeses on the Finnish market. The evaluation of the nutritional quality of fat in these products is of significance to dieticians and to the development of fat products with enhanced nutritional value. Remarkable differences between fatty acid profiles of vegetable fat products were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…Talpur et al (2008) examined Pakistani cheeses and found that saturated fatty acids reached 64.85%. Similar contents of fatty acids were found by Prandini et al (2011), as well as Ritvanen et al (2012). The content of fatty acids in cheese-like products bought in Olsztyn in 2013 was in the range from 49.76% to 52.96% (Paszczyk, 2014).…”
Section: Commercial Cheesessupporting
confidence: 55%
See 4 more Smart Citations
“…Talpur et al (2008) examined Pakistani cheeses and found that saturated fatty acids reached 64.85%. Similar contents of fatty acids were found by Prandini et al (2011), as well as Ritvanen et al (2012). The content of fatty acids in cheese-like products bought in Olsztyn in 2013 was in the range from 49.76% to 52.96% (Paszczyk, 2014).…”
Section: Commercial Cheesessupporting
confidence: 55%
“…Fat, in the rennet ripening cheeses examined by Rutkowska et al (2009), ranged from 20.30% to 28.68%. Full fat cheeses purchased in Finland, and examined by Ritvanen et al (2012), contained fat in the interval from 23.8% to 30.1%. Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations